Implementasi Prinsip Syariah pada Produk Pembiayaan KPR di Bank BTN Syariah Parepare - Nuralika Nuralika; Muhammad Zaky Putra Firman; Ahmad Jaya; Ulan Fajriah (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to examine the implementation of sharia principles in mortgage financing products at Bank BTN Syariah Parepare. It uses a descriptive qualitative method with a case study approach. Data collection techniques include interviews with bank officials and literature review. The results of this study indicate that Bank BTN Syariah Parepare applies sharia principles in KPR financing through the use of murabahah and musyarakah mutanaqisah contracts. The murabahah contract is used for the purchase of ready-to-occupy houses with an agreed profit margin, ensuring that the transaction is free of usury. Musyarakah mutanaqisah is applied to houses under construction, involving a gradual partnership until the customer fully owns the house. In addition to using sharia contracts, Bank BTN Syariah Parepare also applies sharia principles in its human resources (HR) and mortgage financing product marketing. However, there are still challenges in the form of a lack of customer understanding of the concept of margin and sharia contracts, which are often compared to conventional mortgages. Based on this, further education is needed to improve sharia financial literacy among the public.